Early hypoalbuminemia is associated with 28-day mortality in severely burned patients: A retrospective cohort study. Issue 3 (May 2020) - de Tymowski, Christian; Pallado, Simon; Anstey, James; Depret, François; Moreno, Nabilla; Benyamina, Mourad; Cupaciu, Alexandru; Jully, Marion; Oueslati, Haikel; Fratani, Alexandre; Coutrot, Maxime; Chaussard, Maité; et al.
Graphical abstract: Highlights: Early hypoalbuminemia (<6 h after admission) was associated with 28-day mortality. A threshold of 23 g/l at 4H had a Se = 0.81, Sp = 0.70 to predict 28-day mortality. Organ dysfunction occurred more frequently in patients with albuminemia < 23 g/l. Abstract: Background: Hypoalbuminemia is a frequent condition in the first 24 h after a severe burn injury and is associated with worse outcomes. Methodology: We investigated the relation between very early hypoalbuminemia (<6 h after admission) and clinical outcome in a retrospective cohort admitted to our unit for severe burn injuries between 2012 and 2017. Results: 73 severely burned patients were included, with a delay of admission of 3 (2–4) h. In a context of early exogenous supply of albumin, admission and 4H Albuminemia (Alb4 h) were significantly lower in deceased patients (respectively, 34 (29–37) vs 27 (23–30) g/l; p = 0.009 and 27 (24–32) vs 21 (17–27) g/l; p = 0.022) whereas albuminemia ≥6 h were not. The best threshold value of Alb4 h to discriminate 28-day mortality was 23 g/l. Patients with an Alb4 h < 23 g/l had a higher 28-day mortality than patients with an Alb4 h ≥ 23 g/l (42% vs 11%; p =  0.003); adjusted OR = 4.47 (95% CI 1.15–17.36); p =  0.03. Conclusion: In severely burned patients receiving early albumin supply, early hypoalbuminemia is associated with higher mortality whereas later albuminemia (≥6 h) is not. Exploration of whether early albumin infusion (8–12 h post injury) may alter clinical outcome is warranted.